Adherence to antidepressant therapy: clinical experience on the example of agomelatine - N. N. Petrova (Неврология, нейропсихиатрия, психосоматика, 2022)
The review article provides data on the prevalence and treatment problems of depression, highlights the issues of adherence to antidepressant therapy, investigation of the safety and efficacy of agomelatine in real clinical settings. The results of a prospective observational multicenter cohort study of agomelatine in clinical practice are analyzed in detail, taking into account the effect of treatment on the social functioning of patients. The results obtained in a sample representative for depression, including patients with comorbidities, confirm the long-term efficacy and good tolerability of agomelatine in daily practice, which is the basis for adherence to therapy and achievement of the goal of depression treatment